2015
DOI: 10.3389/fnbeh.2015.00147
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplastic effects of transcranial near-infrared stimulation (tNIRS) on the motor cortex

Abstract: Near-infrared light stimulation of the brain has been claimed to improve deficits caused by traumatic brain injury and stroke. Here, we exploit the effect of transcranial near-infrared stimulation (tNIRS) as a tool to modulate cortical excitability in the healthy human brain. tNIRS was applied at a wavelength of 810 nm for 10 min over the hand area of the primary motor cortex (M1). Both single-pulse and paired-pulse measures of transcranial magnetic stimulation (TMS) were used to assess levels of cortical exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
3
25
0
1
Order By: Relevance
“…The physics was applied to each domain at steady state with the initial condition being zero. The source term was taken from the published literature[1] where the power density was 500mW/cm 2 at the scalp surface as presented by Chaieb and colleagues[1]. The head model was assumed to be surrounded by air at room temperature(25°C).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The physics was applied to each domain at steady state with the initial condition being zero. The source term was taken from the published literature[1] where the power density was 500mW/cm 2 at the scalp surface as presented by Chaieb and colleagues[1]. The head model was assumed to be surrounded by air at room temperature(25°C).…”
Section: Methodsmentioning
confidence: 99%
“…Near-infrared (NIR) light has been reported to be able to penetrate the extra-cranial layers like scalp, skull, cerebrospinal fluid and reach the superficial layers of the cerebral cortex due to the optical window. It has been hypothesized that interaction of NIR light with cytochrome c oxidase (CCO) can potentiate the CCO in the mitochondria, a component of the electron transport chain and key complex in energy production[1]. CCO is the primary chromophore in the mitochondria besides the calcium-ion channel (possibly mediated by opsin light absorption).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They used tNIRS at wavelength of 810 nm for 10 min over the hand area of the primary cortex and transcranial magnetic stim at 2.2 Tesla to assess levels of magnetic evoked motor-evoked- potentials of the dorsal interosseous in human brains in 55 healthy volunteers. They concluded that tNIRS is suitable as a tool for influencing cortical excitability and activity [14]. …”
Section: Introductionmentioning
confidence: 99%